Civil Society, Public Action and Accountability in Africa - Devarajan, Shantayanan; Khemani, Stuti; Walton, Michael (2012)
This paper examines the potential role of civil society action in increasing state accountability for development in Sub-Saharan Africa. It further develops the analytical framework of the World Development Report 2004 on accountability relationships, to emphasize the underlying political economy drivers of accountability and implications for how civil society is constituted and functions. It argues on this basis that the most important domain for improving accountability is through the political relations between citizens, civil society, and state leadership. The evidence broadly suggests that when higher-level political leadership provides sufficient or appropriate powers for citizen participation in holding within-state agencies or frontline providers accountable, there is frequently positive impact on outcomes. However, the big question remaining for such types of interventions is how to improve the incentives of higher-level leadership to pursue appropriate policy design and implementation. The paper argues that there is substantial scope for greater efforts in this domain, including through the support of external aid agencies. Such efforts and support should, however, build on existing political and civil society structures (rather than transplanting "best practice" initiatives from elsewhere), and be structured for careful monitoring and assessment of impact.